Monocular Surgery Approach in V pattern Esotropia: A Rare Case Report - Hadi Pradipta, Dhanang; Prastyani, Reni; Loebis, Rozalina; Indriaswati, Luki (Journal of Neonatal Surgery, 2025)
Esotropia, characterized by an inward misalignment of the eyes, presents in various forms, including incomitant deviations such as V-pattern esotropia, which is distinguished by notable differences in gaze direction. V-pattern esotropia is relatively uncommon within the general population. V-pattern esotropia poses a distinct surgical challenge because it is linked to dysfunction of the oblique muscles. Correcting such deviations in individuals with horizontal strabismus can be complex, as both vertical and horizontal misalignments need to be addressed. Usually, surgical approach is to weaken the overactive superior or inferior oblique muscles, depending on the pattern. This case report details the clinical management of a patient diagnosed with V-pattern esotropia. The patient experienced diplopia and blurriness in the right eye for one year, with a history of esotropia that began three years prior. Additionally, he reported occasional visual disturbances and had a family history of strabismus. Initial examination revealed reduced visual acuity in the right eye and suppression of this eye during the Worth Four Dot Test. Further evaluation demonstrated a 15-degree esotropia on Hirschberg testing, accompanied by significant deviations in gaze direction. The Krimsky test indicated V- pattern deviations from the primary gaze position. Surgical intervention consisted of horizontal muscle surgery on the right eye, incorporating the "MALE" (medial to apex lateral to empty) procedure, aimed at restoring the eye to its correct anatomical alignment. Following the surgery, the patient's vision improved, enabling him to read textbooks with ease for his college studies.